National bibliography in the digital age: international recommendations and domestic experience - N. К. Lelikova (Библиосфера, 2021)
The main directions of the development of the national bibliogra-phy in the modern world, the problems of the formation of the system of the national bibliography in Russia, issues related to the current national bibliogra-phy, retrospective national bibliography are presented. The activity of the IFLA Bibliography Section on the regulation of the activity of national bibliographic agencies and the creation of national bibliographic resources is covered. The article describes the activity of the National Bibliographic Agency in Russia (Russian Book Chamber), the National Library of Russia and their role in the creation of a national bibliography in the digital age.